The Thought of Syed Muhammad Naquib Al-Attas on Ta’dib and Ta’lim in Contemporary Islamic Education - Fery Darmawan; Ali Imran Sinaga; Mohammad Al Farabi (AFKARINA: Jurnal Pendidikan Agama Islam, 2026)
This study is motivated by an epistemological crisis in modern Islamic education, characterized by the dominance of secular paradigms and the emergence of a dichotomy between religious and general sciences. This condition calls for a reconstruction of educational concepts rooted in the Islamic intellectual tradition. This research aims to analyze the concept of ta’dib in the thought of Syed Muhammad Naquib al-Attas and its implications for contemporary Islamic education systems. The method employed is qualitative research based on library research, using a content analysis approach on Al-Attas’ major works. The findings indicate that the concept of ta’dib is the most comprehensive educational framework, as it integrates the dimensions of knowledge, faith, and adab into a unified whole. In contrast to ta’lim and tarbiyah, which tend to be partial, ta’dib emphasizes the formation of a civilized human being (insan adabi) as the primary goal of education. Furthermore, Al-Attas criticizes secularism as the main cause of the educational crisis and proposes the Islamization of knowledge as a solution. The implications of this study suggest that the Islamic education system needs to be reconstructed by positioning adab as the fundamental foundation in both curriculum design and the learning process.